Winning - TKincaid, Beth (New York The berkley publishing group, 1995)
Working at the stables in order to pay for her riding lessons, Melissa is disturbed when she sees a boarder mistreating a horse and fears that her intervention may cost her the job that she loves. Original
English Stories
Keywords: English stories